Practice-based research examining effectiveness of exposure-based CBT for youth in a community mental health setting - Emily M. Becker-Haimes; Michal Weiss; Temma Schaechter; Sophia Young; Amanda L. Sanchez (Journal of Mood and Anxiety Disorders)
We examined the naturalistic effectiveness of exposure-based cognitive behavioral therapy (Ex-CBT) for pediatric anxiety and obsessive-compulsive disorder in a community mental health setting. We also characterized adaptations made to Ex-CBT and whether treatment factors varied by whether youth were Medicaid recipients or not. To do so, we conducted a three-year, retrospective chart review of consecutively treated youth in an Ex-CBT treatment center embedded in a community mental health setting (N = 94; 72.3 % Medicaid recipients, 68.1 % female). We abstracted baseline demographic and clinical characteristics, treatment techniques delivered, and treatment process and response variables to examine whether these varied as a function of Medicaid status and identify predictors of treatment response. Medicaid youth were more racially and linguistically diverse than non-Medicaid youth; there otherwise were no differences in baseline demographic and clinical variables. Ex-CBT was delivered in more than twice as many sessions compared to typical clinical trials. Coded session data indicated a more diverse suite of techniques delivered by clinicians not typically included in Ex-CBT protocols (e.g., case management, discussion of cultural and contextual factors) alongside Ex-CBT. Techniques employed by clinicians varied by insurance status. However, response rates were comparable to those seen in clinical trials (51–70 %, depending on response definition). Receiving a higher dose of exposure predicted greater likelihood of treatment response, as did younger age and male gender; Medicaid status and racial/ethnic minority status did not predict response. Overall, data supported Ex-CBT effectiveness in this setting. Ex-CBT was adapted in ways that differed based on whether youth were Medicaid recipients or not.